2015
DOI: 10.1097/scs.0000000000002132
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Preoperative Percutaneous Endoscopic Gastrostomy Placement

Abstract: Patients with a score of 4 or more with this screening scoring system or those patients with an albumin level <3.5 g/dL were at high risk for postoperative feeding tube placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 21 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…Although low serum albumin has been associated with an increased risk of needing a G-tube, the utility of individual laboratory values in determining nutritional status is debated. 23 53 54 55…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although low serum albumin has been associated with an increased risk of needing a G-tube, the utility of individual laboratory values in determining nutritional status is debated. 23 53 54 55…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies are limited by small sample sizes and inclusion of patients undergoing only nonsurgical treatments, treatment of benign disease, small resections amenable to less extensive reconstructions, and/or patients delayed or secondary reconstructions, and heterogeneous analysis that limits statistical validity. 10,23,24 To better address this question, we conducted a retrospective review of the EMR at a large, rural, tertiary care hospital. All patients undergoing resection of head and neck cancers with immediate free-flap reconstruction were included, while those undergoing delayed or secondary reconstruction, only nonsurgical treatments, or those undergoing reconstruction with nonfree-flap techniques were excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, for TORS, 26.7% of surveyed surgeons routinely do not place either nasogastric or gastrostomy feeding access, and only 2.2% of surgeons routinely place a PEG . Chandler et al outlines a preoperative scoring system to predict gastrostomy specific to head and neck reconstruction, with emphasis on low preoperative albumin as a major risk factor for postoperative complications . Mays et al found that perioperative GT with respect to head and neck tumor resection suggests a high‐risk patient with a complicated hospital stay, but also that preoperative GT can protect against poor postoperative outcomes such as prolonged hospital length of stay, wound complications, and weight loss .…”
Section: Discussionmentioning
confidence: 99%
“…7 Chandler et al outlines a preoperative scoring system to predict gastrostomy specific to head and neck reconstruction, with emphasis on low preoperative albumin as a major risk factor for postoperative complications. 20 Mays et al found that perioperative GT with respect to head and neck tumor resection suggests a high-risk patient with a complicated hospital stay, but also that preoperative GT can protect against poor postoperative outcomes such as prolonged hospital length of stay, wound complications, and weight loss. 21 Our data also suggests that postoperative outcomes can be improved by aggressive nutritional screening and early GT in appropriate candidates undergoing robotic primary head and neck tumor resection.…”
Section: Discussionmentioning
confidence: 99%